BET1, BOS1, and SEC22 are members of a group of interacting yeast genes required for transport from the endoplasmic reticulum to the Golgi complex. - Newman, A P (1990)
A subset of the genes required for transport from the endoplasmic reticulum (ER) to the Golgi complex in Saccharomyces cerevisiae was found to interact genetically. While screening a yeast genomic library for genes complementing the ER-accumulating mutant bet1 (A. Newman and S. Ferro-Novick, J. Cell Biol. 105: 1587-1594, 1987), we isolated BET1 and BOS1 (bet one suppressor). BOS1 suppresses bet1-1 in a gene dosage-dependent manner, providing greater suppression when it is introduced on a multicopy vector than when one additional copy is present. The BET1 and BOS1 genes are not functionally equivalent; overproduction of BOS1 does not alleviate the lethality associated with disruption of BET1. We also identified a pattern of genetic interactions among these genes and another gene implicated in transport from the ER to the Golgi complex: SEC22. Overproduction of either BET1 or BOS1 suppresses the growth and secretory defects of the sec22-3 mutant over a wide range of temperatures. Further evidence for genetic interaction was provided by the finding that a bet1 sec22 double mutant is inviable. Another mutant which is blocked in transport from the ER to the Golgi complex, sec21-1, demonstrates a more limited ability to be suppressed by the BET1 gene. The interactions we observed are specific for genes required for transport from the ER to the Golgi complex. The products of the genes involved are likely to have a direct role in transport, as bet1-1 and sec22-3 begin to display their mutant phenotypes within 5 min of a shift to the restrictive temperature.